Evaluation of Total Antioxidant Capacity and Total Oxidant Status of Preterm and Term Breast Milk during the Course of Lactation and within a Nursing Session - Deniz, Asli; Aydemir, Ozge; Cakil Saglik, Adviye; Sekili, Zekiye; Kusku Kiraz, Zeynep; Kar, Ezgi; Tekin, Neslihan (American Journal of Perinatology, 2019)
Objective Breast milk (BM) contains antioxidant molecules which may offer protection against oxidative stress (OS). We aim to investigate oxidant–antioxidant balance in preterm BM during the course of lactation and within a nursing session.Study Design Total antioxidant capacity (TAC) and total oxidant status (TOS) were measured in colostrum, transitional, and mature BM samples of preterm infants born earlier than 34th week of pregnancy and healthy term infants. Oxidative stress index (OSI) was calculated. Foremilk and hindmilk samples were collected separately.Results In colostrum and transitional milk, TAC (p < 0.001 and p = 0.001, respectively) and TOS (p = 0.005 and p < 0.001, respectively) were lower in preterm BM compared with term BM. OSI was also lower in preterm BM, but it was statistically significant only in transitional milk (p < 0.001). TAC was highest in colostrum and decreased through the course of lactation. However, the decrease in TAC was not statistically significant in preterm BM. Lowest values of TOS and OSI were observed in colostrum. In transitional term BM, hindmilk had a better oxidant–antioxidant profile as indicated by lower TOS and OSI.Conclusion Oxidant–antioxidant balance is preserved in BM in every stage of lactation. Preterm BM has lower OSI which may offer benefits to preterm newborn against OS.
Keywords: antioxidants; breast milk; oxidants; oxidative stress; preterm infant